OPTIMISASI TEKNOLOGI SENSOR PADA ALAT BANTU TUNANETRA BERBASIS ARDUINO UNO - Febriyansyah Ramadhan; Ita Rusmala Dewi; Kresna Wibowo Dasa Nugraha (INFOTECH journal, 2025)
Sensor technology offers an innovative solution to enhance the effectiveness of navigation aids for the visually impaired. This study optimizes the performance of the HC-SR04 ultrasonic sensor and Water Level sensor in an Arduino Uno-based device through sensor calibration, refinement of data processing algorithms, and simulations under various environmental conditions. The test results show an improvement in obstacle detection accuracy of up to ±2 cm and a faster response time for the Water Level sensor with an optimal threshold of 750. Algorithm optimization successfully reduces response time by 15%, accelerating buzzer alerts. The system becomes more adaptive to environmental variations, such as narrow spaces and temperature changes. Further development may include adding light sensors or GPS to enhance functionality and user safety.